Effect of Edge Geometry on Cutting Forces in Face Milling with Different Feed Rates - Kundrak, Janos; Markopoulos, Angelos P.; Makkai, Tamas; Karkalos, Nikolaos E. (Manufacturing Technology Journal, 2019)
The fundamental goals of face milling such as high surface quality, dimensional accuracy and productivity can be attained by proper regulation of process parameters, mainly feed rate, depth of cut and cutting speed, but also by taking into consideration the particularities of workpiece material and by selecting the cutting insert with the appropriate geometrical characteristics such as angle κr, rake angle and nose radius. In the present study, the focus is set on the comparison of three different commonly used milling insert types, namely rectangular, round and square regarding cutting forces under various process conditions, with a view to quantitatively evaluate their performance regarding cutting forces and specific cutting forces during face milling of steel workpieces and eventually determine which insert type leads to lower power demand for the same material removed volume. The findings of the present study indicate that the most favorable insert type is the rectangular one, followed by the square and the round one.
Keywords: Face milling; Cutting forces; Specific cutting forces; Milling insert type; Feed rate